Manajemen Pelatihan Program Pemagangan ke Jepang di Lembaga Pelatihan Kerja (LPK) Sakura Purwodadi Kabupaten Grobogan - Rifai, Ahmad; Fakhruddin, Fakhruddin (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze learning management in preparatory training for apprenticeships in Japan at LPK Sakura Purwodadi, covering the functions of planning, implementation, and evaluation. The background of this study stems from the need to improve the quality of Indonesian workers through competency-based training, particularly in facing the demands of Japanese industry, which prioritizes discipline, language skills, and work ethic. The research method used a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation analyzed using the Miles and Huberman model. The results of the study show that training planning is carried out through needs analysis, intensive coordination with Japanese partners, and collaborative curriculum development by instructors according to the ADDIE model. The implementation of training integrates Japanese language learning, work culture, communication simulations, and discipline coaching, in line with the concept of transfer of training and andragogy principles. Training evaluation was conducted periodically through weekly monitoring, competency assessments, and feedback from participants and Japanese partners, reflecting the Kirkpatrick evaluation model. The research conclusion confirms that training management at LPK Sakura has been systematic, relevant to industry needs, and capable of shaping the competencies and character of participants who are ready to work in Japan.